Development of I-Graciass Adoption and Implementation Model at Telkom Education Foundation Lemdikti Knowledge Management Systems Based - Noerma Pudji Istyanto; Muhammad Nasrullah (Journal of Information System and Informatics, 2022)
I-Graciass is one of the digicampus programs under the Directorate of Digital Transformation, Synergy &Performance (DTSP) of the Telkom Education Foundation (YPT) in the form of a smart app & information system as an integrated academic and non-academic management information system. Based on the Vision-Mission, Strategy and Tagline of YPT as The Leader of ICT Education Provider in Indonesia as well as the spirit of carrying out digital transformation in the foundation, so that I-Graciass becomes mandatory to be adopted and implemented in all Higher Education Institutions (Lemdikti) under the guidance of YPT. However, the facts on the ground of the process of adopting and implementing I-Graciass in each Lemdikti are not easy things. For this reason, this research was carried out in order to facilitate the process of adopting and implementing I-Graciass through the method of climbing Knowledge Management Systems (KMS) in all YPT Lemdikti, especially for new universities such as Telkom Institute of Technology Surabaya and other new universities that will later be established by YPT. The results of this study show that the factors that influence the success of the I-Graciass Adoption process at ITTelkom Surabaya and other Lemdikti consist of tennis and non-technical aspects that can refer to the implementation of best practices in the previous lemdikti. In addition, to support the success rate of adoption and implementation, an effective knowledge transfer process is needed through the use and development of the right KMS for an organization and its end users.